2014
DOI: 10.14778/2735508.2735518
|View full text |Cite
|
Sign up to set email alerts
|

Faster set intersection with SIMD instructions by reducing branch mispredictions

Abstract: Set intersection is one of the most important operations for many applications such as Web search engines or database management systems. This paper describes our new algorithm to efficiently find set intersections with sorted arrays on modern processors with SIMD instructions and high branch misprediction penalties. Our algorithm efficiently exploits SIMD instructions and can drastically reduce branch mispredictions. Our algorithm extends a merge-based algorithm by reading multiple elements, instead of just o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…For the layout, we implemented and tested five state-of-the-art SIMD set intersections [6, 7, 15, 39] (see Appendix C.2). For intersections we found that the size of two sets being intersected may be drastically different.…”
Section: Execution Engine Optimizermentioning
confidence: 99%
See 3 more Smart Citations
“…For the layout, we implemented and tested five state-of-the-art SIMD set intersections [6, 7, 15, 39] (see Appendix C.2). For intersections we found that the size of two sets being intersected may be drastically different.…”
Section: Execution Engine Optimizermentioning
confidence: 99%
“…However, for sets that are of similar size, galloping algorithms may have additional overhead. Therefore, like others [7, 15], EmptyHeaded uses a simple hybrid algorithm that selects a SIMD galloping algorithm when the ratio of cardinalities is greater than 32:1, and a SIMD shuffling algorithm otherwise.…”
Section: Execution Engine Optimizermentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al [13] and Inoue et al [14] also used a similar idea to improve the performance of the nested-loop join and the set intersection (merge join).…”
Section: Related Workmentioning
confidence: 99%